Adolescent Hypertension: A Challenge for the Future - Danasekaran, Raja; Mani, Geetha; Annadurai, Kalaivani (Bangladesh Journal of Medical Science, 2016)
Hypertension emerges from a complex interplay of genetic, environmental and behavioral factors. Hypertension in the young which is mostly undiagnosed is increasing in prevalence, with much of the increase being fuelled by the increase in obesity among them. Apart from obesity, factors that have an influence on hypertension are hereditary effects, stress, race and diet. It is well established that blood pressure during childhood and adolescence is a predictor of adult blood pressure, which in turn increases mortality from Cardiovascular, Cerebro vascular and other complications, clearly underscores the importance of identification and treatment of hypertension among them. Bangladesh Journal of Medical Science Vol.15(1) 2016 p.5-9